Strategi Penguatan Moderasi Beragama di Rohis Madrasah Aliyah Negeri - Finan Ahsani Taqwim (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2022)
Various phenomena of radicalism in the Rohis  need special attention. This journal aims to analyze the actors and effective strategies for strengthening religious moderation in the Rohis of the Public Madrasah Aliyah. The research method used is literature review and discussion with the stakeholders involved. The strategy for strengthening religious moderation in Rohis MAN requires the support of various actors, namely the Ministry of Religion, the Religious Moderation Working Group, Heads of Madrasahs, Rohis coaches, Moderate Islamic Community Organizations and members of the Rohis themselves. The steps taken need to adapt to the characteristics of each actor, such as questionnaires and interviews for Rohis coaches, reviewing existing regulations, facilitating funding at madrasahs, Islamic study activities and fun activities as well as dissemination religious moderation books for students.